Synthesis of Some 2-Amino-5-substituted-1,3,4-oxadiazole Derivatives in the Acetic Acid - Sanjeev Kumar (E-Journal of Chemistry)
An environmentally benign method for the preparation of 2-amino-5-substituted-1,3,4-oxadiazoles (1a-n) at platinum electrode through the electrooxidation of semicarbazone at room temperature is reported. The electrolysis were carried out at controlled potential in acetic acid solvent using lithium perchlorate as supporting electrolyte in an undivided cell assembly. Square shaped plates of platinum were used for working as well as counter electrode and a third electrode saturated calomel electrode was used as a reference electrode for the measurement of potential difference between two electrodes during the electrolysis.